Meteorology measurements during OASIS Barrow field intensive Spring 2009, Version 1.0 ... - Guenther, A. (UCAR/NCAR - Earth Observing Laboratory, 2012)
A measurement intensive campaign was carried out in Barrow, Alaska in spring 2009 as part of the Ocean Atmosphere Sea Ice Snowpack (OASIS) program. This dataset contains three-dimensional wind velocities measured at 2 heights (~ 2 m agl and 6 m agl) using sonic anemometers (Applied Technologies, Sonic Anemometer/Thermometer model (SATI/3K)). Also, from the measured speed of sound, virtual potential temperature was also obtained. Wind velocities and virtual potential temperature were acquired at 10 Hz. Meteorological variables such as wind speed and direction were obtained from vector-averaging the horizontal wind velocities over 1 minute intervals. Turbulent fluxes, such as friction velocities and sensible heat flux, were obtained from covariances of wind velocities and temperature over 15 minute averages. The longer time scale allows for adequate sampling of larger atmospheric eddies that contribute to the measured flux. Wind speeds and direction are accurate to +/- 0.03 m/s and +/- 0.1 degrees, ...